アンドレス・ダリオ・イゼタ ( コルドバ国立大学哲学人文学部人類学科(アルゼンチン) ) ガブリエル・ロクサナ・カッタネオ ( コルドバ国立大学哲学人文学部人類学科(アルゼンチン) ) - Izeta, Andres Dario (2024)
The aim of this paper is to explore the evolution and current state of archaeological databases in Argentina, with a focus on their role in heritage management and research. This study will examine the development of digital tools in Argentine archaeology, tracing their evolution from the 1960s to the present day. A key advancement has been the creation of open-access databases, such as BADACor, which facilitate the organization and sharing of archaeological data. Additionally, this paper will discuss how Argentina’s commitment to open access aligns with global trends towards applying FAIR principles, which ensure that archaeological data is findable, accessible, interoperable, and reusable.